Evaluation of the structure of the regular component of the departmental programs of habits and healthy lifestyles, Colombia, 2014-2015 (2018)
Community programs of physical training are a promising strategy to struggle against sedentariness. In Colombia, there is a National Program for Healthy Habits and Lifestyle. To ascentain the program structure from its general evaluation purpose becomes essential to know its relevance and coherence. is study aims to evaluate the structure and variability of the regular component of the Province Programs for Healthy Habits and Lifestyle, Colombia 2014-2015. is research consisted of a documentary analysis, an assessment of logical models, and a semi-structured interview. e logic processing of the data showed differences regarding the diagnosis and a consensus was found regarding the setting out of objectives, which are set in reply to the needs and problems of the population and are addressed through hardly variable strategies. e goals proposed in the programs, for future developments, should take into account the user’s behavior and context. © 2018 Pontificia Universidad Javeriana. All rights reserved.